Modern Education: The Advantage and Effectiveness of Distance Learning - Navruzova, Elena Pavlovna; Isroilova, Guzal Ravshanovna; Khasanov, E. R. (International Journal on Human-Computing Studies, 2022)
This article discusses distance learning and its advantages. The concept of "distance learning" is revealed, the model of the introduction of distance learning into the educational process is defined.